PENGEMBANGAN TES ONLINE MENGGUNAKAN GNOMIO DALAM PEMBELAJARAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) PADA SISWA SEKOLAH MENENGAH ATAS - Panggah Ridho Barrakaalahu; Aloysius Mering; Indri Astuti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
The purpose of this study was to produce an online test using gnomio in ICT learning for high school students. To achieve the research objectives, the Research and Development (R&D) method was used with the development design procedure using Borg and Gall. The research instrument uses documentation and questionnaires. Data analysis techniques for validation of material and media experts and user trials using descriptive statistics. The results of the research and development trial show that the online test using gnomio is proven to be feasible to use as an online test using gnomio. The percentage of response values in the first stage of the trial was 78.75% with the "Positive" criteria, the percentage of the response values in the second stage of the trial was 84.38% with the "Positive" criteria, and the percentage of the response values in the field trials was 91.33%. with the criteria of "Very Positive". From the results of research and development of online tests using Gnomio, it is very helpful in conducting online test implementation and assessment. The conclusion of this study is that through the development of online tests using Gnomio for high school students, it is very helpful in the implementation of learning evaluation media in the form of online tests that can be run either on computer or smartphone media.